1980
DOI: 10.1017/s0022215100090265
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear tuberculosis

Abstract: Fourteen cases of tuberculous otitis media are reported. With the declining incidence of pulmonary tuberculosis, the number of reported cases of tuberculous otitis media has become scanty. Nowadays the so-called classical signs of the lesion such as a profuse discharge, profound hearing loss, facial paralysis and multiple perforations, are hardly ever seen. Surgical intervention when done under cover of anti-tubercular drugs has no deleterious effect on the result of surgery. In order not to miss tuberculous o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
4

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 9 publications
3
60
0
4
Order By: Relevance
“…3 Superadded infection makes it difficult to demonstrate tubercular bacilli in ear discharge, and culture also provides a low yield. 26 Culture for Mycobacterium tuberculosis (performed using BACTEC system) was positive in 25% (3) cases in this study, while others have found culture positivity to the extent of 16.13% (Yaniv E, 1987), 28.57% (Plester et al, 1980) and 90.91% (Windle Taylor PC and Bailey CM, 1980). 6,7,23 Mantoux test was positive in 83.33% (10) cases, while it was 100% in the study of Yaniv.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…3 Superadded infection makes it difficult to demonstrate tubercular bacilli in ear discharge, and culture also provides a low yield. 26 Culture for Mycobacterium tuberculosis (performed using BACTEC system) was positive in 25% (3) cases in this study, while others have found culture positivity to the extent of 16.13% (Yaniv E, 1987), 28.57% (Plester et al, 1980) and 90.91% (Windle Taylor PC and Bailey CM, 1980). 6,7,23 Mantoux test was positive in 83.33% (10) cases, while it was 100% in the study of Yaniv.…”
Section: Discussionmentioning
confidence: 54%
“…27,28 Chest X-ray showed evidence of active pulmonary tuberculosis in 66.67% (8 cases). Results from other reports include a positivity to the extent of 42.86% (Plester et al, 1980), 51.61% (Yaniv E, 1987) and 93.02% (Singh B, 1991). 7,8,23 The imaging modality of choice in cases of TOM is CT-scan.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A characteristic clinical finding is granulomatous middle ear mucosa which is pale and a vascular. Multiple perforations of the tympanic membrane cannot be substantiated as a hallmark of tuberculous otitis media [10]. As the pathologic process advances inexorably, the granulations lead to attico-antral blockage and destruction of nearby tissues such as skull base or the tegmen tympani, leading to tuberculous meningitis or skull base osteomyelitis [10,11].…”
Section: Discussionmentioning
confidence: 99%